Differences of Microbiomes Found in Non-Inflammatory and Inflammatory Lesions of Acne Vulgaris - Jusuf NK; Putra IB; Sari L (Dove Medical Press, 2020)
Nelva Karmila Jusuf, Imam Budi Putra, Lovena Sari Department of Dermatology and Venerology, Faculty of Medicine, Universitas Sumatera Utara, Medan, IndonesiaCorrespondence: Nelva Karmila JusufDepartment of Dermatology and Venerology, Faculty of Medicine, Universitas Sumatera Utara, Medan, North Sumatera 20995, IndonesiaTel +62 811651324Email edelweiss.flowers13@gmail.comPurpose: Bacterial activity and inflammation both influence acne vulgaris (AV) formation. Cutibacterium acnes is considered as an actor involved in inflammation of AV. Besides Cutibacterium acnes, other microbiomes found in AV may also play a role in the pathogenesis. This research was conducted to overview microbiomes found in non-inflammatory and inflammatory lesions of AV.Patients and Methods: An observational descriptive study with cross-sectional approach was designed. Sample collection was performed with 40 subjects with AV. In every patient, both non-inflammatory (closed comedone) and inflammatory (pustule) lesion samples were collected by swab. Afterward, bacterial culture was performed, continued by bacterial identification.Results: In non-inflammatory lesions, the growth of nine bacterial species was observed from 40 samples. In an anaerobic culture, Cutibacterium acnes (17,5%) was identified. In aerobic cultures, different bacterial species were found including Staphylococcus epidermis (52.5%), Staphylococcus hominis (12.5%), Staphylococcus haemolyticus (7.5%), Micrococcus luteus (7.5%), Leuconostoc mesentroides (7.5%), Staphylococcus aureus (5%), Kocuria varians (5%), and Staphylococcus vitulinus (2.5%). In inflammatory lesions, nine bacterial species were found, in which was the anaerobic culture we identified Cutibacterium acnes (25.0%). Aerobic cultures have revealed the growth colonies of Staphylococcus epidermidis (42.5%), Staphylococcus hominis (22.5%), Staphylococcus aureus (12.5%), Staphylococcus haemolyticus (10.0%), Leuconostoc mesentroides (5.0%), Staphylococcus cohnii (2.5%), Staphylococcus arlettae (2.5%), and Dermacoccus nishinomyaensis (2.5%). Two mixed bacterial growths were observed in non-inflammatory lesions, while four mixed bacterial growths were found in inflammatory lesions.Conclusion: Differences in bacterial isolates were observed both in non-inflammatory and inflammatory lesions of AV.Keywords: acne vulgaris, microbiome, non-inflammatory, inflammatory